2015
DOI: 10.1073/pnas.1424391112
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of age-related macular degeneration-like pathology by complement factor H

Abstract: SignificanceAge-related macular degeneration (AMD) affects approximately one-third of Americans over 70 and is characterized by lipoprotein-rich sub-retinal pigmented epithelium (sub-RPE) deposits. Substantial evidence has emerged that implicates complement factor H (CFH) in the pathogenesis of AMD. Here, we conduct an in vivo analysis to elucidate the role of CFH in AMD pathology. We show that (i) CFH and lipoproteins compete for binding in the sub-RPE extracellular matrix such that decreasing CFH leads to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(172 citation statements)
references
References 99 publications
5
157
0
3
Order By: Relevance
“…CFH normally protects self tissues from complement-induced destruction by binding to a range of surface signals including glycoproteins and C-reactive protein. In addition to the binding of CFH to MDA noted above, it was also reported that CFH inhibits lipoprotein binding toward Bruch’s membrane [67]. The breach of Bruch’s membrane and the intrusion of blood vessels into the retina are the hallmarks of wet AMD [52], which are consistent with our finding of high association in Degradation of extracellular matrix and Common pathway of fibrin clot formation in Fig.…”
Section: Resultssupporting
confidence: 90%
“…CFH normally protects self tissues from complement-induced destruction by binding to a range of surface signals including glycoproteins and C-reactive protein. In addition to the binding of CFH to MDA noted above, it was also reported that CFH inhibits lipoprotein binding toward Bruch’s membrane [67]. The breach of Bruch’s membrane and the intrusion of blood vessels into the retina are the hallmarks of wet AMD [52], which are consistent with our finding of high association in Degradation of extracellular matrix and Common pathway of fibrin clot formation in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Our data also point to downstream lipid peroxidation-related products, specifically CEP and 4-HNE, in the etiology of AMDf (37,38). Interactions between mutated Complement factor H (CFH), a strong risk factor for human AMD, and high dietary lipids and cholesterol lead to an AMD phenotype that resembles the HG phenotype (15). Although we did not observe changes in Cfh in our mice, the underlying pathobiology may be similar.…”
Section: Discussionmentioning
confidence: 49%
“…Despite lacking a macula, the mouse retina shows many AMDf and has been useful for relating risk factors for AMD, including cigarette smoking, diet, and inflammation (10,(14)(15)(16)(17)(18). Here we tested the hypothesis that changing from an HG to an LG diet even during maturity can delay or arrest AMDf.…”
Section: Significancementioning
confidence: 99%
“…Compelling mechanistic evidence of a role for complement dysregulation was lacking until the recent work by Toomey et al (Toomey et al, 2015). Using aged CFH +/− mice given a high fat diet, this group found that decreased CFH led to increased basal deposit formation and decreased vision, as quantified by ERG changes.…”
Section: The Role Of Inflammation On the Rpementioning
confidence: 99%